Effect of disease severity on upper extremity muscle strength, exercise capacity, and activities of daily living in individuals with pulmonary arterial hypertension - Buse Özcan Kahraman; İsmail Özsoy; Serap Acar; Ebru Özpelit; Bahri Akdeniz; Can Sevinç; Sema Savcı (KARE Publishing, 2017)
Objective: Pulmonary arterial hypertension (PAH) is a rare disease. Although muscle strength, exercise capacity, quality of life, and activities of daily living of patients with PAH are affected, it is not known how they are affected by disease severity. The purpose of the present study was to investigate effects of disease severity on upper extremity muscle strength, exercise capacity, and performance of activities of daily living in patients with PAH. Methods: Twenty-five patients with disease severity classified according to the New York Heart Association (NYHA) as functional class II (n=14) or class III (n=11) were included in the study. Upper-extremity exercise capacity and limitations in performing activities of daily living were assessed with 6-minute pegboard and ring test (6PBRT) and the Milliken activities of daily living scale (MAS), respectively. Shoulder flexion, elbow extension, elbow flexion muscle strength, and handgrip strength were measured with dynamometer. Results: There were no significant differences in age, gender, body mass index, or mean pulmonary artery pressure between groups (p>0.05). The 6PBRT, MAS, and elbow flexion (right) and grip strength (right and left) results were significantly lower in NYHA III group than in NYHA II group (p=0.004, p=0.002, p=0.043, p=0.002 and p=0.003, respectively). There was no significant difference in shoulder flexion, elbow flexion (left), or elbow extension between groups (p>0.05). Conclusion: Results suggest that upper extremity exercise capacity, elbow flexion muscle strength (right), and handgrip strength decrease and that limitations in activities of daily living grow as disease severity increases in patients with PAH. When planning rehabilitation programs, disease severity should be considered and evaluations and treatments for the upper extremities should be included.